Modulated Model Predictive Current Control of a Four-Leg Inverter - Rojas-Lobos, F (Institute of Electrical and Electronics Engineers Inc., 2020)
A novel modulated model predictive current control for a two-level four-leg voltage source inverter is proposed in this paper. The proposed scheme is designed by combining the operating principles of traditional predictive control with the three-dimensional space vector modulation to enhance the output power quality, while producing fixed switching frequency operation and fast dynamic response for the four-leg inverter. In contrast to the classical predictive control which applies the switching state corresponding to optimal cost function, the proposed controller uses three active vectors and a zero vector to optimize the cost function. Finally, the switching states for four-leg inverter are produced by a modulation stage containing nine-segment switching pattern similar to the classical three-dimensional space vector modulation. The proposed control scheme is validated through simulations considering three-phase unbalanced reference currents and loads. © 2020 IEEE.